2015
DOI: 10.1186/s40064-015-1364-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism study at 15 autosomal locus in central Indian population

Abstract: The analysis of 15 autosomal STR locus (TH01, D3S1358, vWA, D21S11, TPOX, D7S820, D19S433, D5S818, D2S1338, D16S539, CSF1PO, D13S317, FGA, D18S51, D8S1179) was done in 582 healthy unrelated individuals (Male-366, Female-216) originating from the various geographical regions of Madhya Pradesh, India. All locus fall under Hardy–Weinberg equilibrium except TPOX. These STR loci were highly informative and discriminating with combined power of discrimination (CPD) >0.99999. Locus wise allele frequencies of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 38 publications
4
20
0
Order By: Relevance
“…After DNA extraction and PCR, analysis was performed on 3500XL genetic analyzer, and statistical evaluation was done as described before [ 4 ]. The peak height threshold was 50 RFU for heterozygous and 200 RFU for homozygous alleles.…”
Section: Descriptionmentioning
confidence: 99%
“…After DNA extraction and PCR, analysis was performed on 3500XL genetic analyzer, and statistical evaluation was done as described before [ 4 ]. The peak height threshold was 50 RFU for heterozygous and 200 RFU for homozygous alleles.…”
Section: Descriptionmentioning
confidence: 99%
“…The allele frequencies at the 15 autosomal STRs in the Lahore-Christian population were compared with those from 16 other populations using population differentiation test as shown in Supplementary Table 4 . Significant differences were observed after Boneferroni’s correction ( p ≤ 0.0002) at 15/15 loci with Mongol, 14/15 African American 26 , 27 , Caucasian (12/15) 27 , Uganda Yousafzai and Kashmiri (11/15) 16 , 18 , 28 , Balochi, Punjabi, central India (7/15) 14 , 23 , 38 . While differences at small numbers of loci for Nepalese, Sindhi (3/15), Karnataka and Bangladeshi (2/15) 21 , 24 , 25 , 39 were observed.…”
Section: Resultsmentioning
confidence: 99%
“…A neighbour joining (NJ) tree (Fig. 2 a) based on the Nei's genetic distance, constructed using POPTREE-2 software, was used to investigate the genetic affinity between the studied (admixed and Teli ) populations and the reported Indian populations namely, the Konkanastha Brahmins (Maharashtra) [ 22 ]; the Mahadev Kolis (Maharashtra) [ 22 ]; the Iyengars (Tamil Nadu) [ 22 ]; the Kurumans (Tamil Nadu) [ 22 ]; the Yerukulas (Andhra Pradesh) [ 23 ]; the Koras (West Bengal) [ 24 ]; the Baniyas (Punjab) [ 25 ]; the population of Jharkhand [ 26 ]; the population of Uttar Pradesh [ 27 ]; the population of Rajasthan [ 28 ]; the populations of Central India [ 29 ]; and the pooled populations belonging to the geographical boundaries of India [ 30 ]. The NJ tree revealed that the studied admixed and Teli populations of Maharashtra pooled into one cluster with the Konkanastha Brahmin s of Maharashtra and the Kurumans of Tamil Nadu.…”
Section: Main Textmentioning
confidence: 99%